Separation of Chromium(VI) Metal in Wastewater Using Electrocoagulation Method with NaCl Coagulant - Farhan Baehaki; Wasiyah Khusna Fadhilah; Mila Karmila (Department of Chemistry - Universitas Bangka Belitung, 2022)
Waste has become an environmental problem that needs attention in its handling. Metal Cr (VI) is one of the components of a very dangerous pollutant produced by industrial activities, such as textiles. In fact, there are still many textile industry players who do not treat their waste because they feel that the processing requires expensive upfront costs. Therefore, this research was conducted to perform a sewage treatment system with a separation technique using an alternative method, namely electrocoagulation using NaCl coagulant. The research was conducted at the Laboratory of Applied Chemistry and Toxicology at the Rajawali Health Institute. The sample used is a sample of liquid waste taken directly from a textile industry in Bandung, Indonesia. The results showed a decrease in the levels of Cr (VI) after the electrocoagulation process until it reached a percentage value of 64.02%. Based on this, it can be said that the electrocoagulation method is effective enough to be used as a simple treatment technique to reduce the levels of Cr (VI) metal in wastewater.